Role of staphylococci in mastitis in sheep. Issue 3 (19th August 2019) - Vasileiou, Natalia G. C.; Chatzopoulos, Dimitris C.; Sarrou, Stela; Fragkou, Ilektra A.; Katsafadou, Angeliki I.; Mavrogianni, Vasia S.; Petinaki, Efthimia; Fthenakis, George C.
Abstract: Staphylococci have been isolated from various sites of the body of healthy sheep, as well as from many infections of those animals, the main one being mastitis. The objective of this review is to appraise the importance and significance of staphylococci in causing mastitis in ewes. The review includes a brief classification and taxonomy of staphylococci and describes the procedures for their isolation and identification, as well as their virulence determinants and the mechanisms of resistance to antibacterial agents. Various staphylococcal species have been implicated in staphylococcal mastitis and the characteristics of isolates are discussed with regards to potential virulence factors. Staphylococcal mastitis is explicitly described, with reference to sources of infection, the course of the disease and the relevant control measures. Finally, the potential significance of staphylococci present in ewes' milk for public health is discussed briefly.